Linking weather and climate information services (WCIS) to Climate-Smart Agriculture (CSA) practices - Mabhaudhi, Tafadzwanashe; Tinashe Lindel Dirwai; Cuthbert Taguta; Aidan Senzanje; Abera, Wuletawu; Ajit Govid; Dossou-Yovo, Elliott; Aynekulu, Ermias; Chimonyo, Vimbayi Grace Petrova (Elsevier, 2025)
Objective(s): This study synthesises existing knowledge on the linkages between Weather and Climate Information Services (WCIS) and Climate-Smart Agriculture (CSA) practices. Specifically, it addresses the following questions: (1) What is the current status of knowledge on WCIS and CSA in the global south, specifically the African continent?, (2) Are WCIS effectively tailored and linked to CSA practices and technologies to improve agricultural water management (AWM) amongst smallholder farmers?, and (3) How can linking WCIS and CSA facilitate the identification, appraisal and prioritization of regionally differentiated and context-specific climate-appropriate technologies and policies that enhance agricultural water management at various levels (field, farm, scheme, and catchment)? Methods: The study used the Preferred Reporting Items for Systematic and Meta-Analysis Protocol (PRISMA-P) guidelines. It involved the search of the Scopus and Web of Science databases for peer-reviewed articles, books, and grey literature focussed on the global south. Results: The results revealed that seasonal forecasts were the main WCIS available to farmers who utilised them to plan predominantly for irrigation and water harvesting activities. Daily forecasts were linked to practices such as irrigation. The study also revealed that temperature and rainfall (amount and distribution) were predominantly disseminated to farmers through extension services. The dominant CSA practices used by farmers were carbon-smart (e.g., composting), water-smart practices (improved varieties, irrigation, RWH), weather-smart practices (IPM & crop insurance), and nitrogen-smart practices (organic fertiliser, crop diversification). Advisories on carbon-smart practices generally aligned closely with the start and end of rainfall information, while the water-smart practices were corroborated with the rainfall onset, end of rainfall season, and rainfall intensity. Weather smart practices were strongly linked to drought, temperature, and rainfall distribution, whereas nitrogen smart practices were linked with the end of rainfall and temperature. Conclusions: The study concluded that distinct linkages exist between WCIS and various CSA categories. The study argues that increasing access to WCIS can facilitate the adoption and scaling of CSA practices.